Xanthan gum as a water-based binder for P3-Na2/3Ni1/3Mn2/3O2 - Zilinskaite, Silvija; Reeves-McLaren, Nik; Boston, Rebecca (Frontiers in Energy Research, 2022)
P3-Na2/3Ni1/3Mn2/3¬O2 (P3-NNM) is a promising cathode material for Na-ion batteries, though large volume expansions during cycling mean that challenges around suitable binders remain. This paper reports the use of xanthan gum as a water-soluble, easy to handle, and sustainable biopolymer binder in conjunction with a P3-Na2/3Ni1/3Mn2/3¬O2 positive electrode material. The conditions for recovering pristine P3-NNM powders following water-based processing are established, and the electrochemical performance of cells prepared using xanthan gum binder are compared to the more traditional polyvinylidene fluoride. Comparable discharge capacities are observed regardless of binder choice, at ca. 115 mAh g-1 (77 mAh g-1 after 50 cycles; 0.1 C between 2.0 and 4.2 V). The xanthan gum binder cells also show similar rate capability and slightly higher capacities at faster c-rates vs. polyvinylidene fluoride, making xanthan gum a viable alternative to the traditional organic binders for water-stable cathode materials.